Nutrition – facts and myths - Verbanac Donatella; Maleš Željan; Barišić Karmela (Acta Pharmaceutica)
Taking responsibility for your life, among other factors, means also considering what to eat and which nutrition pattern to follow. Everyone needs to think about what they put on the plate and which ingredients should be avoided. Food, as such, will never be a drug or medication, like a painkilling tablet relieving pain in a short amount of time, for example. However, proper nutrition is our ally in the prevention of diseases, maintaining balance in our body and our mind. By following the main principles of a healthy diet, the physiological homeostasis can be managed, as well as faster recovery from disease achieved.